Contrasting Effects of Intensive Cultivation and Paddy Field Abandonment on the Invasion of Ludwigia grandiflora (Michx.) Greuter & Burdet in the Lowlands of Manokwari, Indonesia: Pengaruh Kontras Lahan Sawah Intensif dan Lahan Bekas Sawah terhadap Invasi Ludwigia grandiflora (Michx.) Greuter & Burdet di Dataran Rendah Manokwari, Indonesia - Slamet Arif Susanto; Pramesty Wulan Ramadhanty; Trigarcia Maleachi Randa (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2026)
The invasive plant Ludwigia grandiflora (Michx.) Greuter & Burdet poses a serious threat to tropical wetland ecosystems, particularly abandoned paddy fields. The invasive potential of this plant results from the interaction between its regenerative capacity, as reflected by population size, seed production, soil seed bank, and germination rate. This study aimed to analyze individual abundance, soil seed bank potential, and germination rates of L. grandiflora across two land-use types, namely intensively cultivated paddy fields and abandoned paddy fields that have been left uncultivated for five years, in Sidey District, Manokwari Regency, West Papua, Indonesia. Abundance was assessed using the quadrat method, while seed production and germination rates were evaluated through seed counts per capsule and the seedling emergence method at two soil depths. The results showed that the abundance of L. grandiflora in intensively cultivated fields ranged from 80 to 160 individuals m⁻², whereas in abandoned paddy fields it ranged from 50 to 90 individuals m⁻². Welch’s t-test revealed that the abundance of L. grandiflora differed significantly between the two land types studied (p < 0.05). Likewise, the number of seeds per capsule was significantly higher in intensively cultivated paddy fields (p < 0.05). In contrast, abandoned paddy fields exhibited a higher soil seed bank and higher germination rates (p < 0.05) than intensively cultivated fields. Soil samples from greater depths showed lower germination rates of L. grandiflora, as well as longer germination times, compared with surface soils. The abundance, seed production, soil seed bank, and germination rate can serve as early indicators of the invasive potential of L. grandiflora. These findings indicate that agricultural activities, particularly fertilization, play an important role in enhancing the invasive potential of L. grandiflora in lowland paddy field ecosystems